The data imperative : how digitalization is reshaping management, organizing, and work - Schildt, Henri (Oxford University Press, 2020)
Companies across all industries are engaging in digital transformation. Henri Schildt provides an in-depth look at how data and algorithms are reshaping management practices, organizational structures, corporate culture, and work roles, and presents 'the data imperative' as a framework for understanding digitalization as a new normative mind-set.